Exploring burnout among teachers: a comparative analysis across public, charter, and private elementary school environments - Krause Koch, Carrie, author; Gloeckner, Gene W., advisor; Fothergill, Wendy, advisor; Enns, Kellie, committee member; Frederiksen, Heidi, committee member (Colorado State University. Libraries, 2025)
This quantitative study utilized secondary data from the nationally representative 2020-2021 National Teacher and Principal Survey (NTPS), conducted by the U.S. Department of Education, to investigate the relationships between teacher burnout and work environment factors among 13,560 full-time K-5 elementary school teachers in U.S. public, charter, and private schools. To ensure generalizability to the U.S. teaching population, the NTPS's complex sampling design was accounted for by applying required data weights during all analyses. The study addressed three primary research questions. First, burnout levels significantly differed across school types (X2 (2) = 102.89, p < .001). Private school teachers reported the highest burnout, followed by public and charter school teachers. Second, significant differences were found across all work condition variables—workload, classroom control, teacher collective control, recognition, leadership, teaching community, parent support, student apathy, and school types. Pairwise comparisons indicated that public and charter school teachers shared similar perceptions regarding leadership, teaching community, recognition, student apathy, and parent support, while private school teachers differed significantly from both groups. Differences emerged between education management organization (EMO) and non-EMO charter school teachers and religious and non-religious private school teachers in several work condition variables; however, effect sizes were trivial. The final research question examined correlations between work conditions and burnout across school types. Strong positive correlations were observed between leadership and the teaching community, and between leadership and recognition. The relationship between student apathy and parent support remained consistently weak and negative across all school types (ρ = -0.25). Burnout exhibited strong negative correlations with leadership and the teaching community with moderate effect sizes across all school types. Charter school teachers showed the strongest negative correlation between burnout and leadership (ρ = -0.57). Similarly, charter school teachers reported the strongest positive correlation between leadership and the teaching community (ρ = 0.77). Findings highlight common patterns and variations in the associations between work conditions and burnout across public, charter, and private school teachers. This study compared teacher burnout and work environment factors across public, charter, and private schools, highlighting significant differences. The aim was to determine if different school types and working conditions impact teacher burnout and identify potential environmental factors to mitigate burnout.
Keywords: charter; private; work conditions; National Teacher and Principal Survey; burnout; public